Study of a Three Phase Induction Motor Load Fstimation System by Low-Cost Piezoelectric Sensor - Lucas, Guilherme Beraldi [UNESP]; Castro, Bruno Albuquerque de [UNESP]; Rocha, Marco Aurelio [UNESP]; Andreoli, Andre Luiz [UNESP]; Tsuzuki, MDG; Junqueira, F. (Ieee, 2018)
Three-phase induction motors (TIMs) play a key role in the industrial scenario. Due to their robustness and efficacy, coupled with increasingly accessible variable frequency control methods, TIMs have been used to drive many types of loads. At the same time as the increase in the use of TIM occurs, consequently, the importance of detecting fails in its operation increases as well. An analysis tool that demonstrates good results for a noninvasive diagnosis of damages in induction motors is the study of the signals from mechanical vibration in the machine. In this paper, these signals were processed in order to estimate the mechanical load present on the motor shaft and, to make it possible, low-cost piezoelectric sensors were used for transducing the mechanical vibrations into electrical signals. Besides that, for the data processing, study techniques were applied using RMS voltage and cross-correlation. Thus, it was possible to determine pattern changes of the signals in function of the imposed load and, in this way, to estimate it. It was found that, even without structural malfunctions or disturbances in the electrical network, the load attached to the shaft, on its own, changes the vibratory behavior of TIM.
Keywords: Three-phase induction motor; Low-cost piezoelectric sensor; Signal processing